2017
DOI: 10.15406/mojt.2017.03.00058
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metals in Cassava Mill Effluents with Saccharomyces cerevisiae isolated from Palm Wine

Abstract: Nigeria is World leading producer of cassava accounting for about 20% of global output. Rudimentary equipment is used for cassava processing into several products such as high quality cassava flour by smallholders that dominate the cassava processing sector in Nigeria. The properties of the wastewater (cassava mill effluents) often exceed the limits for effluents to be discharge into the environment (land and surface water) as specified by Federal Environmental Protection Agency. Cassava mill effluents induce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…CME is a major waste from cassava processing, an agro business in Nigeria [16][17][18][19][20][21][22][23], Cassava processing alters soil microbial characteristics (Table 2 and 3), physicochemical properties (Table 4), Heavy metals concentration (Table 5), cation and anions exchange (Table 6), soil enzymatic activity (Table 7), soil particle size, bulk density and porosity (Table 8) and lipase, and elevates urease concentration [77,82].…”
Section: Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…CME is a major waste from cassava processing, an agro business in Nigeria [16][17][18][19][20][21][22][23], Cassava processing alters soil microbial characteristics (Table 2 and 3), physicochemical properties (Table 4), Heavy metals concentration (Table 5), cation and anions exchange (Table 6), soil enzymatic activity (Table 7), soil particle size, bulk density and porosity (Table 8) and lipase, and elevates urease concentration [77,82].…”
Section: Soilmentioning
confidence: 99%
“…In Nigeria, cassava farming and processing into useful food items is a major source of livelihood to several families especially in rural areas [11,[16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Nigeria is the largest producers of cassava in the world [4,11,12]. During the processing cassava mill effluents (waste water) is a major liquid wastes that are discharged into the soil without any form of treatment [6][7][8][9][13][14][15][16]. Thereby causing an alteration in microbial [17] and physicochemical constituents of the receiving soil over a prolong period of time [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby causing an alteration in microbial [17] and physicochemical constituents of the receiving soil over a prolong period of time [12]. Studies have indicated that the constituents of the wastes could be improved upon when treated with Saccharomyces cerevisiae [6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Solid wastes are another group of wastes stream that is poorly managed in most urban and rural areas in Nigeria. Solid wastes result from several human activities including market [11,12], abattoir [13], household activities [14], agricultural processing such as oil palm processing (viz: empty fruit bunch, chaff, palm press fibre, palm kernel shell) [15][16][17][18], cassava processing (viz: cassava peels) [1,2,[19][20][21][22][23][24][25][26] among others. Solid wastes also include remain of scrap metals, plastics, woods, etc.…”
Section: Introductionmentioning
confidence: 99%